(untitled) (Bangladesh Journal of Medical Science, 2013)
Hypokalemic periodic paralysis is an uncommon manifestation of thyrotoxicosis and the condition is most commonly reported in young Asian men. Patient often presents with acute onset symmetrical flaccid muscle paralysis and proximal limb muscles may be more severely involved compared to distal muscles. Thyroid swelling as well as features of thyrotoxicosis may not be overt. A very high index of suspicion is often required for the diagnosis of thyrotoxic periodic paralysis. Treatment of throtoxicosis prevents further episodes of paralysis. We report a case of thyrotoxic periodic paralysis in a young male. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 320-321 DOI: http://dx.doi.org/10.3329/bjms.v12i3.12719